Calligonum polygonoides L. as Novel Source of Bioactive Compounds in Hot Arid Regions: Evaluation of Phytochemical Composition and Antioxidant Activity - Mukesh K. Berwal; Shravan M. Haldhar; Chet Ram; Sandip Shil; Ramesh Kumar; Jagan S. Gora; Dhurendra Singh; Dilip K. Samadia; Manoj Kumar; Mohamed Mekhemar (Plants, 2021)
Calligonum polygonoides L. (Phog) is an endemic perennial herb that is highly resistant to all type of abiotic stresses and dominant biomass as well as phytochemicals producer in its natural habitat of the “Thar Desert” of Rajasthan, India. The present study was conducted to evaluate the effect of extreme environmental conditions on the phenolic, flavonoids, tannin content, and total antioxidant activities of C. polygonoides foliage harvested during different months. It exhibited a significant variation in the content of phenolic compounds, flavonoids, tannins, and antioxidant activity with harvesting time and all parameters are positively correlated to each other. The highest phenolic compounds and antioxidant activity was observed during severe winter and summer months, when monthly average environmental temperature was lowest and highest of the year, respectively. On the basis of the results, two harvests of C. polygonoides foliage during June and December are advised to maximize the phenolic compound production with highest antioxidant activity. These results demonstrate C. polygonoides, which is a dominant biomass producer under the harsh climatic conditions, can be an important source for the development of the functional foods rich in antioxidants in hot arid regions.